Statement in regard to the Minister of Health's White Paper on the establishment of "A National Health Service." (1944)
1944 1944 1940s 18 pages reference to this service is that the term 'hospital service' comprises the usual ancillary hospital service for 'ambulances and other purposes'. With this brief reference a vital and essential service to every citizen is passed over, and is regarded as an 'ancillary'. If the scope of the Hospital Services are to be extended as envisaged in the White Paper, then a similar extension must of necessity apply to the Ambulance Services, which at the moment in many areas relies entirely upon private enterprise or voluntary effort, It is, in our submission, useless to develop one aspect of the Health Services without making provision for a similar development for that service which has to 'feed' the former. Further we submit that the time has arrived when the Ambulance Service personnel should, in the interests of the public whom it has to serve in the dealing with accident cases or removal of patients to the various hospitals and institutions, be efficiently trained and certificated, and brought to some degree comparable with the nursing profession. In brief it appears to us as if, in its consideration of the proposals outlined in the White Paper, the requirements of the major vested interests have predominated. The Minister appears to have taken the line of least resistance. The rightful claims of the citizen have been jettisoned and subordinated to the clamourings of these who feel that the citizen should be fitted in' to their demands and requirements. SPECIFIC SURVEY. 1. The National Government, on receiving and surveying the Social Security Scheme proposals by the Beveridge Departmental Committee, accepting Assumption B of the Report, envisaging the development of a National Health Service. The Government's proposals as to the policy and organisation of such a comprehensive Health Service have now been published after prolonged travail and much negotiation, and have been embodied in the White Paper. The policy is disappointing in many respects. It is NOT a comprehensive service. It is NOT a Health or Health Workers' service but only a medical service for personal treatment mainly of the sick or disabled. There is no imaginative grasp of the country's health needs, primarily as regards organised popular health Education; Social environment problems; industrial disease hazards, and especially concerning prevention of ill-health and administrative co-operative handling, with the advantage of consultative and advisory Whitley or Joint Consultative Machinery for contact with the health Workers of all grades actually working the scheme. 2. The Government accept the principle of the need for the universality of the scheme of free equal terms to every person in the community, but the principle of uniformity is violated at every turn, as every patient or doctor will be allowed, in obeisance to the cries of freedom and the attitude of snobbery or unorthodoxy to contract out of the service at the penalty of paying for the medical service he thinks he requires outside the Governmental arrangements. No contracting out is apparently to be allowed by exemption from the obligation of contributing to the scheme, but only in respect of being granted permission to pay for medical service or advice outside the scheme at the penalty of personal extra cost. 5. The policy is a contradictory one. For example the 'single comprehensive service for all' is favourably regarded as the most natural development', while the dual Hospital system with favourable financial terms to the Voluntary Hospitals is accepted, and the medical treatment and examination service is deliberately multi-form so as to suit all types of medical employees e.g., the medical practice can be conducted on contract terms at an Health centre on full-time or part-time employment, or in grouped practice (by co-partnership of private practitioners at one or more surgeries) or in seperate practice, (a pracitioner [practitioner] working single-handed in isolation even on a part-time competitive basis). This is a Compromise Policy to meet the objections of all types of practitioners, but each different type of medical service, whilst it can be tolerated, will increase the administrative difficulties of working the scheme and probably add to the administrative expense. 4. The White Paper policy is not proposed as the final settled Health Policy (if there is one) but 'to be freely examined and discussed'. In other words the White Paper does not represent the Government's final conclusions. What that policy will be when the discussions have taken place, no one can foretell. This Union, representative of the organised Health Workers, is entitled to submit its entitlements and suggestions. Many of the medical objections, as expressed so far, are clearly based on misgivings or forebodings, rather than on an impartial survey of the Government's document 4. 292/847/2/43